2022
DOI: 10.1002/pon.5963
|View full text |Cite
|
Sign up to set email alerts
|

Perceived risk and risk reduction behaviours of female first‐degree relatives of breast cancer patients attending care at Uganda cancer institute

Abstract: Objective:The objective of this study was to assess the perceived risk of breast cancer (BC) and adoption of risk reduction behaviours among female first-degree relatives (FDRs) of BC patients attending care at the Uganda Cancer Institute (UCI). Methods:A cross-sectional study was performed using a questionnaire to collect data between March to October 2019. Adult female FDRs of patients attending care at UCI were recruited consecutively. Breast cancer perceived risk was assessed using a verbal measure; 'My ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Twentyeight articles were screened for full-text review. Thirteen articles were subsequently identified for inclusion in the review (Ainembabazi et al, 2023;Audrain et al, 1999;Bastani et al, 1999;Bloom et al, 2006;Hajian et al, 2011;Houts et al, 1991;Lipscomb et al, 2020;Liu et al, 2017;Nasiriani et al, 2017;Oleske et al, 2007;Richardson et al, 1996;Tao et al, 2017;.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twentyeight articles were screened for full-text review. Thirteen articles were subsequently identified for inclusion in the review (Ainembabazi et al, 2023;Audrain et al, 1999;Bastani et al, 1999;Bloom et al, 2006;Hajian et al, 2011;Houts et al, 1991;Lipscomb et al, 2020;Liu et al, 2017;Nasiriani et al, 2017;Oleske et al, 2007;Richardson et al, 1996;Tao et al, 2017;.…”
Section: Search Resultsmentioning
confidence: 99%
“…Female FDRs, including mothers, sisters, and daughters of BC patients, have a 1.5‐ to 3‐fold greater risk of developing BC during their lifetime than the general population (Braithwaite et al., 2018). However, the FDRs of BC patients frequently lack details about their individual BC risks to take early detection measures (Ainembabazi et al., 2023). The BC screening rates for the FDRs of BC patients are low (Kirca et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review of the duration of time from symptom onset to the first consultation with a health professional in breast cancer patients, Petrova et al 17 demonstrated the role that literacy and education, stigma, low socioeconomic status and social support play in delaying help-seeking in this population. Ainembabazi et al 18 have demonstrated the link between perception of risk and seeking of screening in female relatives of patients with breast cancer in Uganda.…”
Section: Overview Of the Special Issue Contentmentioning
confidence: 99%
“… 17 demonstrated the role that literacy and education, stigma, low socioeconomic status and social support play in delaying help‐seeking in this population. Ainembabazi et al 18 have demonstrated the link between perception of risk and seeking of screening in female relatives of patients with breast cancer in Uganda.…”
Section: Overview Of the Special Issue Contentmentioning
confidence: 99%